PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM LIFE SKILL DI SANGGAR KEGIATAN BELAJAR KABUPATEN LUWU (Studi pada Pelatihan Menjahit Pakaian) - syamsulbakhri syamsul (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2022)
The problem of this study is how the description of the implementation of the life skills of the clothing sewing training program in empowering the community is carried out by the Non-Formal Education Unit of the Luwu Regency Learning Activity Center. The approach used in this study is a quality approach with a type of action research. The focus of this study is on: (1) Planning of the clothing sewing training life skills program, (2) Implementation of the clothing sewing training life skill program, and (3) Evaluation of  the clothing sewing training life skill program. The target of the study was the Head of the Non-Formal Education Unit of the Luwu Regency Learning Activity Workshop, Pamong Belajar, Auxiliary Tutors, Instructors and trainees in clothing sewing skills at the Non-Formal Education Unit of the Luwu Regency Learning Activity Center. Data collection was carried out using interview, observation and documentation techniques. The data analysis technique used is a qualititative descriptive analysis technique. The results showed that: (1) Before learning training in sewing women's clothing and alma mater suits, it is necessary to identify learning needs and learning resources so that the learning material is really in accordance with the learning needs of prospective trainees and not just the wishes of prospective participants; (2) Synergy between the government, the private sector / business world, and the community in the implementation of life skills education (sewing women's clothing and alma mater suits) can be carried out by designing the involvement of the government, private / business and the community.